2013
DOI: 10.1093/abbs/gmt003
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphism of transforming growth factor-β1 in Egyptian patients with type 2 diabetes and diabetic nephropathy

Abstract: Role of the transforming growth factor-b1 (TGF-b1) gene polymorphisms located at codons 10 and 25 in the genetic predisposition to type 2 diabetes (T2D) and in diabetic nephropathy (DN) in Egyptian patients was investigated. A case control study was done for 99 unrelated Egyptian patients with T2D (50 DN 2 and 49 DN 1) and 98 age-and sex-matched healthy controls. TGF-b1 T869C (codon 10) and G915C (codon 25) polymorphism detection was done by amplification refractory mutation system method. DN 1 patients were y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…Further genetic model analysis also revealed that the CC genotype provided a higher risk as compared to the TC + CC genotype combination for ESRD manifestation. Similar trends were reported by a study on an Egyptian population where frequency of C-allele was higher in cases (both total T2D and T2D with ESRD) as compared to controls, and the TC genotype was providing 2-2.7-fold risk towards T2D and ESRD development (El-Sherbini et al, 2013). TGF-b1 g.869T > C polymorphism was observed to provide risk towards DN in Mexican (Valladares-salgado et al, 2010) and Chinese populations (Wong et al, 2003) and towards ESRD in a North Indian population (Mittal and Manchanda, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…Further genetic model analysis also revealed that the CC genotype provided a higher risk as compared to the TC + CC genotype combination for ESRD manifestation. Similar trends were reported by a study on an Egyptian population where frequency of C-allele was higher in cases (both total T2D and T2D with ESRD) as compared to controls, and the TC genotype was providing 2-2.7-fold risk towards T2D and ESRD development (El-Sherbini et al, 2013). TGF-b1 g.869T > C polymorphism was observed to provide risk towards DN in Mexican (Valladares-salgado et al, 2010) and Chinese populations (Wong et al, 2003) and towards ESRD in a North Indian population (Mittal and Manchanda, 2007).…”
Section: Discussionsupporting
confidence: 85%
“…In renal diseases, elevated expression of TGF-β1 can induce renal hypertrophy and promote excessive accumulation of ECM proteins, thus leading to renal fibrosis [55]. To be more specific, TGF-β1 is significantly enhanced in the renal tissues of patients with DN, especially in mesangial cells of diabetic glomeruli [56]. Therefore, it is likely that these pathological changes caused by TGF-β1 may contribute to the initiation and progression of DN.…”
Section: Inflammation and Oxidative Stress-related Genesmentioning
confidence: 99%
“…The hotspot mainly focuses on T869C (rs1800470; Leu10/Pro10; T29C, codon 10) in exon 1, which is located at position 10 in the signal peptide [55]. The T869C gene polymorphism has been linked with the risk of DN in different ethnic groups, such as Chinese [55], Egyptians [56], Mexicans [58], and Caucasians of Polish descent. The T869C gene polymorphism was notably different between diabetic patients with and without DN, and the DN group had a higher frequency of the CC/CT genotype [59].…”
Section: Inflammation and Oxidative Stress-related Genesmentioning
confidence: 99%
See 2 more Smart Citations